Effectiveness of an eye health education program on healthy behaviors against myopia progression in children - Rivera-Hurtado, Melanie S. (2025)
Objective. To evaluate the effectiveness of an ocular health education program on healthy behaviors related to myopia progression in fifth- and sixth-grade primary school children in 2023. Methods: An analytical, quasi-experimental, longitudinal, and prospective study was conducted. The independent variable was the educational program, while the dependent variable was healthy behaviors regarding myopia progression. The sample consisted of 116 primary school students, divided into an intervention group and a control group. Descriptive statistical analysis was performed using Excel, and inferential analysis was conducted using SPSS v.25, employing McNemar's test and the chi-square test. Results: A statistically significant association was found between the dependent variable and the dimensions of knowledge, attitudes, and practices in the intervention group (p < 0.05; 95% CI). Before the intervention, 48.2% of participants had a high level of knowledge, which increased to 85.7% after the program (p < 0.001). Positive attitudes rose from 28.6% to 85.7% (p < 0.001), and adequate practices improved from 32.1% to 76.8% (p < 0.001). Conclusions: The ocular health education program proved to be effective in improving healthy behaviors related to myopia progression in primary school children.